Multi-Scale Convolutions Meet Group Attention for Dense Prediction Tasks - Vo, Xuan Thuy (Springer Nature, 2024)
Lecture Notes in Networks and Systems (LNNS,volume 882); The 13th Conference on Information Technology and Its Applications (CITA 2024) ; pp: 360-371.